Digital pills: Leveraging whatsapp for antibiotic resistance awareness - Sari, A Anditha; Susanto, Agus; Setiyanto, Riyan (Universitas Bunda Mulia, 2025)
The escalating threat of antibiotic resistance, driven by misuse and overuse of antibiotics, poses a severe public health crisis that requires immediate and innovative solutions. Education on proper antibiotic use is crucial in combating this issue, particularly among community health cadres who play a pivotal role in disseminating health information. This study evaluates the influence of an educational intervention delivered via audio-visual media through WhatsApp on enhancing the knowledge and attitudes of Integrated Health Pos (Posyandu) and Family Welfare Movement (PKK) cadres about antibiotic resistance. A pretest-posttest design was adopted, involving 100 participants from rural areas in Kebak Kramat Subdistrict, Karanganyar Regency, Central Java. Questionnaires assessed participants' knowledge and attitudes both before and after the intervention, which consisted of educational audio-visual content shared through WhatsApp. The findings revealed a significant improvement in knowledge, as evidenced by a Mann-Whitney U test Z-value of -2.044 (p=0.041) when comparing Posyandu and PKK cadres. However, no significant change was observed in attitudes, with a Z-value of -0.944 (p=0.345). These results indicate that while the intervention effectively increased knowledge about antibiotic resistance, it had limited impact on altering attitudes. The study underscores WhatsApp’s potential as a practical and accessible platform for delivering health education in rural settings. Nevertheless, it also highlights the necessity for complementary approaches to foster meaningful attitude changes and encourage sustained behavioral adaptations in antibiotic use. Future interventions should explore integrating interactive and participatory methods to address these challenges more effectively.